Hybrid Performance and Heterosis for Yield and Agronomic Traits of Quality Protein Maize (Zea mays L.) Inbred Lines Adapted to Mid-altitude Agroecology of Ethiopia - Lemi Yadesa Mideksa; Sentayehu Alamerew; Berhanu Tadesse (Agro Bali : Agricultural Journal, 2022)
Maize is a primary crop in most farming systems and staple food of the rural population in abundant of the mid-altitude sub- humid agro-ecologies of Ethiopia. Nearly 88% of maize produced in Ethiopia is consumed as food, both as green and dry grain. Yet, it has low protein content since it is normal maize, with poor protein quality limited by deficiencies in lysine and tryptophan and has an excess of leucine and isoleucine. Suggestions on hybrid performance and heterosis of QPM inbred for grain yield and its components is vital to design suitable breeding strategies for the development of nutritionally enhanced maize varieties. A line x tester analysis involving 36 crosses generated by crossing nine elite maize inbred lines with four testers and four checks were evaluated for yield and yield related traits at Bako and Jimma. The objectives were to evaluate mean performance and the magnitude of heterosis for quality protein maize inbred lines, adapted to mid altitude agroecology of Ethiopia. The genotypes were evaluated in alpha lattice design replicated three times. Analyses of variances showed significant (p<0.05 or p<0.01) mean squares due to genotypes in each and across locations for most traits studied, indicating the existence of appropriate genetic variability. The crosses, L5xT2, L7xT2, L8xT1, L8xT2, L3xT2, L5xT1, and L1xT1 showed higher grain yield. The estimated mid and better parent heterosis for grain yield across locations for all crosses displayed positive and highly significant variances which ranged from 386.6% to 111.2% and 288.9% to 72.2%, respectively. From this study, about 77.78% of crosses had better potential for grain yield. The results attained in this experiment suggest that the hopeful potentials of the identified inbred lines for further breeding of QPM for the mid-altitude agroecology of Ethiopia.